Developing A Cross-Cultural Conceptual Framework for the Validation of the Advanced Clinical Solutions (ACS)-SP: Assessing Social Perception in Latinx Populations. (30th August 2019) - Forte, M; Nestor, P
Abstract: Objective: Develop a cross-cultural conceptual framework for the validation of the Advanced Clinical Solutions (ACS) Social Perception subtest to effectively assess Latinx populations. Method: The framework serves to examine and evaluate the composition of the normative sample of the ACS-SP using eight key variables taken from the ECLECTIC framework, specifically education (e.g., literacy), acculturation levels (e.g., race, ethnicity), language (e.g., proficiency), economics (e.g., SES), communication styles, testing comfort, intelligence conceptualization, and context of immigration (Fujii, 2018). In addition, the model assesses the normative sample in reference to the intersectionality of identities (Cole, 2009; Wadsworth et al., 2016) across cultural and demographic variables that may influence the expression of emotion, and consequently, the interpretation of ACS-SP results. The model applies an Etic-Emic approach to address the question of cross-cultural validity of the ACS-SP (Cheung, van de Vijver & Leong, 2011). Finally, the model can be applied to examine the ACS-SP in relation to cultural intelligence (CQ), a more recently established construct defined as an individual's ability to function effectively inter-culturally (Ang, Rockstuhl, & Tan, 2015). Discussion: A large body of research has shown that the expression and measurement of social cognitive abilities are greatly influenced by cultural factors (Elfenbein & Ambady, 2002). For example, studies have shown that the expression of these abilities may be greatly influenced by cultural differences in display rules. Likewise, it is equally important to consider key cultural variables such as those related to socioeconomic status (SES), demographics, and identity in the neuropsychological assessment of social perception in Latinx populations. Therefore, the model conducts a cross-cultural analysis of the ACS-SP. References: Ang, S., Rockstuhl, T., & Tan, M. L. (2015). Cultural intelligence and competencies. International Encyclopedia of Social and Behavioral Sciences, 2, 433-439. Cheung, F. M., Leung, K., Fan, R. M., Song, W. Z., Zhang, J. X., & Zhang, J. P. (1996). Development of the Chinese personality assessment inventory. Journal of Cross-Cultural Psychology, 27 (2), 181-199. Cole, E. R. (2009). Intersectionality and research in psychology. American psychologist, 64 (3), 170. Elfenbein, H. A., & Ambady, N. (2002). On the universality and cultural specificity of emotion recognition: a meta-analysis. Psychological Bulletin, 128 (2), 203. Fujii, D. E. M. (2018) Developing a cultural context for conducting a neuropsychological evaluation with a culturally diverse client: The ECLECTIC framework. The Clinical Neuropsychologist, 32 (8), 1356-1392, DOI: 10.1080/13854046.2018. 1435826 . Wadsworth, L. P., Morgan, L. P., Hayes-Skelton, S. A., Roemer, L., & Suyemoto, K. L. (2016). Ways to boost your research rigor through increasing your cultural competence (part 1 of 2). The Behavior Therapist.